(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Shutko V. V. Modern look at the problems of physical education and formation of the individuality of a student. The article is dedicated to combining physical education with other types of education: intellectual, moral, aesthetic, labor, to the direction of the formation of the individual student, in purpose to solve some important problems that have developed in secondary school physical education.